2013
DOI: 10.1177/1757913913486874
|View full text |Cite
|
Sign up to set email alerts
|

Investigating obesity risk-reduction behaviours and psychosocial factors in Chinese Americans

Abstract: Nutrition educators working with Chinese Americans need to address self-efficacy in preparing plant-based, home-cooked meals and making healthy choices at fast-food restaurants with portion control. Concrete and perceived barriers such as lack of time and convenience need to be addressed in nutrition education interventions. Educators need to identify new channels and media outlets to disseminate practical, easy-to-implement behaviours for obesity risk reduction that are socially acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…reported that among the structures related to health belief model, the perceived barriers and self-efficacy were the only predicting factors for nutritional behavior among Asian adults residing in USA. [ 30 ] Consistent with the results of the present study, their results showed that besides existing barriers such as lack of social support in access to beneficial nutrients and adequate information to attain enough knowledge about healthy nutrition, understanding the threat, resulting from inappropriate nutrition, has no effect on nutritional behavior. The relationship between nutritional attitude and mothers’ educational level, in addition to the lack of relationship between psychological factors with the economic status and fathers’ educational level indicated the mothers’ key role in providing appropriate nutritional motivation among the adolescents and improvement of their nutritional conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…reported that among the structures related to health belief model, the perceived barriers and self-efficacy were the only predicting factors for nutritional behavior among Asian adults residing in USA. [ 30 ] Consistent with the results of the present study, their results showed that besides existing barriers such as lack of social support in access to beneficial nutrients and adequate information to attain enough knowledge about healthy nutrition, understanding the threat, resulting from inappropriate nutrition, has no effect on nutritional behavior. The relationship between nutritional attitude and mothers’ educational level, in addition to the lack of relationship between psychological factors with the economic status and fathers’ educational level indicated the mothers’ key role in providing appropriate nutritional motivation among the adolescents and improvement of their nutritional conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is likely that after adolescents’ dependence on families’ provision of healthy foods disappears and when they enter the teenage period and adulthood, their nutritional pattern may change under new conditions. In conditions of independency for food provision, adolescents’ interpersonal factors such as their attitude[ 29 ] and understanding of the threat[ 30 ] may act as more important determinants for selection of their favorite food.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important, improvements in knowledge of nutrition and health effects of exercise, proves to be a significant predictor of all three outcome measures. Because the Asian diet is generally thought to be healthy, most Asian communities do not think about aspects of their diet that are unhealthy and do not consider changes that may have occurred in their diets and the diets of their children since moving to the US [43,44,45]. Changing these perceptions to improve knowledge of healthier eating and exercise must be a key component of effective health campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…no. 55rich in fruits and vegetables as the mean of promoting healthy living.The behavior to reduce the risk of obesity risk in relation to psychosocial factors was recently investigated in USand foreign-born Chinese Americans[98]. The main reasons for the prevention of adopting obesity riskreducing behavior related to the convenience of consuming fast food meals, cost, lack of time to prepare home-cooked meals, and the physical environment of unhealthy food.…”
mentioning
confidence: 99%